Respons Ekstrak Hipofisa Kambing Terhadap Fekunditas Ikan Betok (Anabas testudineus) - Muarofah Ghofur; Muhammad Sugihartono; Ulil Azmi; Lara Anggraini (Universitas Batangahari Jambi, 2023)
The production of betok fish has experienced overfishing and resulted in a decrease in productivity, therefore one of the efforts made to help success in spawning betok fish can be done by stimulating factors related to the reproductive system, namely by stimulating the work of hormones in stimulating gonadal maturation in artificial spawning with hypophysation method. This study aims to look at the response of goat pituitary extract to the fecundity of betok fish (A. testudineus, Bloch). This research was conducted for 30 days, using 4 treatments with 3 replications, with details of treatment P0: Control, treatment P1: Goat Pituitary Extract 0.05 ml/kg, Treatment P2: Goat Pituitary Extract 0.2 ml/kg, and treatment P3 : Goat Pituitary Extract 0.35 ml/kg. The results of the study using the best goat pituitary extract in the P2 treatment (0.2 ml/kg Goat Pituitary Extract) produced the highest fecundity, namely 8349 eggs produced. The results of water quality measurements showed that the pH value was 7.6 – 7.7. water temperature is 270C – 300C, dissolved oxygen (DO) is 2.9 – 4.4 mg/L. and the content of ammonia (NH3) during the study was 0.012 – 0.013 mg/L.